Implementation of the model of content and language integrated learning for students of economic specialities - Cherednichenko, Galina; Nikitenko, Olga (My University, 2022)
The article considers a content and language integrated learning (CLIL) approach, which is currently characterized in the world scientific and methodical literature as one of the innovative approaches to the organization of bilingual education and provides for the simultaneous implementation of two learning goals in two subject areas – language and subject; various interpretations of its essence are given, its varieties, possibilities, and peculiarities of implementation in bilingual education are highlighted by applying its basic principles and strategies. The article reveals the experience of the department's teachers in creating the author's course "Introduction to International Economics in English", and describes its structure, content, and other aspects of its development and practical use. The work offers examples of the use of content and language integrated learning aproach in training of students of economic specialties, as well as examples of tasks for 4 types of language skills, reading, writing, speaking, and listening, which contribute to the effective development of professional and linguistic competencies.

У статті розглядається предметно-мовний інтегрований підхід (CLIL), який на сьогодні у світовій науково-методичній літературі характеризується як один із інноваційних підходів до організації білінгвального навчання та передбачає одночасну реалізацію двох цілей навчання у двох предметних галузях. – мова і предмет; подано різні тлумачення його сутності, висвітлено його різновиди, можливості та особливості реалізації в білінгвальному навчанні шляхом застосування його основних принципів і стратегій. Стаття розкриває досвід викладачів кафедри по створенню авторского курсу “Вступ до міжнародноі екомоміки англійською мовою”, описана його структура, зміст та інші аспекти його розробки і практичного використання. В роботі запропоновані приклади використання інтегрованого предметно-мовного навчання для студентів економічних спеціальностей, а також приклади завдань по 4 видам мовних навиків, читання, письмо, мовлення и слухання, що сприяють ефективному розвитку професійних і лінгвістичних компетенцій.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; content and language integrated learning (CLIL); students; economic specialities; bilingual education; integration; предметно-мовний інтегрований підхід (CLIL); студенти; економічні спеціальності; білінгвальна освіта; інтеграція